Penggunaan Ekstrak Pelepah Pisang Ambon sebagai Sanitizer Kerabang terhadap Daya Tetas Telur Itik Lokal - Rukmiasih; Ramadhan, F. K.; Afnan, R. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2019)
The use of KMnO4 and formalin 40% for fumigation of hatching machine and hatching eggs has potential hazards to safety and health. Some previous studies have shown that banana pseudostem extract can act as an antimicrobial. This study aimed to examine the use of ambon banana pseudostem extract (Musa paradisiaca var. Sapientum) with concentrations of 10%, 20%, and 30% as eggshell sanitizer to the hatchability of local duck eggs. The results showed eggs hatchability that use of 10% banana pseudostem extract still lower than eggs hatchability that use fumigation. The higher concentration of banana pseudostem extract can reduce the hatchability. Therefore, it is necessary to try experiment use banana peseudostem extract with concentration lower than 10%.